Career Decision-Making Processes of Young Adults With First-Episode Psychosis. (May 2018) - Boychuk, Christa; Lysaght, Rosemary; Stuart, Heather
The first episode of psychosis often emerges during young adulthood, when individuals are pursuing important educational and career goals that can become derailed because of the development of major impairments. Past research has neglected the developmental nature of employment and education decisions that young adults with first-episode psychosis make within the context of their lives. The purpose of this grounded theory study was to advance a model of the career decision-making processes of young adults with first-episode psychosis, and the influences that affect their career decision-making. The career decision-making of young adults with first-episode psychosis emerged as a multistaged, iterative process that unfolded over three phases of illness, and was affected by several internal and environmental influences. These findings suggest the phase of illness and career decision-making stage should be considered in future vocational programming for young adults with first-episode psychosis.